Precipitation over urban areas in the western Maritime Continent using a convection-permitting model - Argüeso, Daniel; Di Luca, Alejandro; Evans, Jason P. (Climate Dynamics, 2016)

Seasonal mean temperature changes control future heat waves - Argüeso, Daniel; Di Luca, Alejandro; Perkins‐Kirkpatrick, Sarah E.; Evans, Jason P. (Geophysical Research Letters, 2016)
Abstract Increased temperature will result in longer, more frequent, and more intense heat waves. Changes in temperature variability have been deemed necessary to account for future heat wave characteristics. However, this has been quantified only in Europe and North America, while the rest of the globe remains unexplored. Using late century global climate projections, we show that annual mean temperature increases is the key factor defining heat wave changes in most regions. We find that commonly studied areas are an exception rather than the standard and the mean climate change signal generally outweighs any influence from variability changes. More importantly, differences in warming across seasons are responsible for most of the heat wave changes and their consideration relegates the contribution of variability to a marginal role. This reveals that accurately capturing mean seasonal changes is crucial to estimate future heat waves and reframes our interpretation of future temperature extremes. , Key Points The influence of projected temperature variability changes on future heat waves varies across the globe Future heat waves are primarily controlled by annual mean changes, except in Europe and North America Mean seasonal warming is responsible for over 95% of projected heat wave changes in most region

Evaluating the representation of Australian East Coast Lows in a regional climate model ensemble - Di Luca, Alejandro; Evans, Jason; Pepler, Acacia; Alexander, Lisa; Argüeso, Daniel (Journal of Southern Hemisphere Earth System Science, 2016)

Using large-scale diagnostic quantities to investigate change in East Coast Lows - Ji, Fei; Evans, Jason P.; Argueso, Daniel; Fita, Lluis; Di Luca, Alejandro (Climate Dynamics, 2015)

Resolution Sensitivity of Cyclone Climatology over Eastern Australia Using Six Reanalysis Products* - Di Luca, Alejandro; Evans, Jason P.; Pepler, Acacia; Alexander, Lisa; Argüeso, Daniel (Journal of Climate, 2015)
Abstract The climate of the eastern seaboard of Australia is strongly influenced by the passage of low pressure systems over the adjacent Tasman Sea due to their associated precipitation and their potential to develop into extreme weather events. The aim of this study is to quantify differences in the climatology of east coast lows derived from the use of six global reanalyses. The methodology is explicitly designed to identify differences between reanalyses arising from differences in their horizontal resolution and their structure (type of forecast model, assimilation scheme, and the kind and number of observations assimilated). As a basis for comparison, reanalysis climatologies are compared with an observation-based climatology. Results show that reanalyses, specially high-resolution products, lead to very similar climatologies of the frequency, intensity, duration, and size of east coast lows when using spatially smoothed (about 300-km horizontal grid meshes) mean sea level pressure fields as input data. Moreover, at these coarse horizontal scales, monthly, interannual, and spatial variabilities appear to be very similar across the various reanalyses with a generally stronger agreement between winter events compared with summer ones. Results also show that, when looking at cyclones using reanalysis data at their native resolution (approaching 50-km grid spacing for the most recent products), uncertainties related to the frequency, intensity, and size of lows are very large and it is not clear which reanalysis, if any, gives a better description of cyclones. Further work is needed in order to evaluate the usefulness of the finescale information in modern reanalyses and to better understand the sources of their differences.

Quantifying the overall added value of dynamical downscaling and the contribution from different spatial scales - Di Luca, Alejandro; Argüeso, Daniel; Evans, Jason P.; De Elía, Ramón; Laprise, René (Journal of Geophysical Research: Atmospheres, 2016)
Abstract This study evaluates the added value in the representation of surface climate variables from an ensemble of regional climate model (RCM) simulations by comparing the relative skill of the RCM simulations and their driving data over a wide range of RCM experimental setups and climate statistics. The methodology is specifically designed to compare results across different variables and metrics, and it incorporates a rigorous approach to separate the added value occurring at different spatial scales. Results show that the RCMs' added value strongly depends on the type of driving data, the climate variable, and the region of interest but depends rather weakly on the choice of the statistical measure, the season, and the RCM physical configuration. Decomposing climate statistics according to different spatial scales shows that improvements are coming from the small scales when considering the representation of spatial patterns, but from the large‐scale contribution in the case of absolute values. Our results also show that a large part of the added value can be attained using some simple postprocessing methods. , Key Points A rigorous methodology that allows evaluating the overall benefits of high‐resolution simulations The most reliable source of added value is the better representation of the spatial variability Substantial added value can also be attained using simple postprocessing methods

Effects of City Expansion on Heat Stress under Climate Change Conditions - Argüeso, Daniel; Evans, Jason P.; Pitman, Andrew J.; Di Luca, Alejandro (PLOS ONE, 2015)

Evaluating reanalysis-driven CORDEX regional climate models over Australia: model performance and errors - Di Virgilio, Giovanni; Evans, Jason P.; Di Luca, Alejandro; Olson, Roman; Argüeso, Daniel; Kala, Jatin; Andrys, Julia; Hoffmann, Peter; Katzfey, Jack J.; Rockel, Burkhardt (Climate Dynamics, 2019)

Projected change in characteristics of near surface temperature inversions for southeast Australia - Ji, Fei; Evans, Jason Peter; Di Luca, Alejandro; Jiang, Ningbo; Olson, Roman; Fita, Lluis; Argüeso, Daniel; Chang, Lisa T.-C.; Scorgie, Yvonne; Riley, Matt (Climate Dynamics, 2019)